The impact of merger and acquisition on firms operating performance; post analysis of Malaysia Companies in 2013 / Nurwaaqiah Mohd Zam - Mohd Zam, Nurwaaqiah (2017)
Merger and acquisition is one of the most frequently used strategy for companies that searching for grow in business and also provide a competitive advantage. While merger and acquisition global trend is increasing, the trend is contrast with trend for Malaysia which in Malaysia they are facing a downward trend of merger and acquisition started from year 2013. So, a total of 25 companies from different sector excluded financing sector that going through merger and acquisition with deal value more than 50 million Ringgit Malaysia. The operating performance is being measured by ROE as the dependant variable. While the independent variables included 10 different ratios which is CR, QR, DER, GPM, NPM, ATO, ITO, ARTO, APTO and Sales in order to have more accurate analysis at the end of this research. The study is using panel regression analysis which is PLS method as the main regression in order to determine the impact of merger and acquisition to companies operating performance. At the end, the result shows that there is positive significant impact in operating performance after merger and acquisition in term of their NPM and ATO. Different result for CR, QR, DER, GPM, ITO, ARTO, APTO and Sales as they did not show a significant impact on the operating performance although some of them is showing a positive relationship with the operating performance. In conclusion, M&A is actually did not have significant impact on the firm's operating performance.